Anatomical Structures at Risk in Percutaneous Distal Bunionette Correction - Shrey Nihalani BS, BA; Mila Scheinberg MD, MS; Ashish Shah MD (Foot & Ankle Orthopaedics, 2024)
Introduction/Purpose: Bunionette deformity affects 23% of the population and has numerous surgical options, including a minimally invasive approach (MIA) to decrease complications. Percutaneous surgery is favored by patients as it decreases pain, inflammation, and noticeable incision sites. Three possible osteotomy sites have been identified: proximal, diaphyseal, and distal. The study investigates the anatomic structures at risk during distal osteotomy of bunionette deformity using a Shannon burr. The distal osteotomy site was on average greater than 8mm from the extensor digitorum longus and adductor digiti minimi while it was 1.64mm from the lateral dorsal cutaneous nerve. The study highlighted the challenges posed by minimally invasive approaches to treating bunionette deformity and the need for cautious consideration when utilizing percutaneous methods. Methods: Eleven fresh frozen below-knee amputated foot and ankle cadavers were used for this study. Cadavers were allowed to thaw for 12 hours at room temperature before performing any tissue handling. All cadavers were visually inspected for evidence of gross pathology. Fluoroscopic radiographs were used to inspect for evidence of preexisting pathology of the fifth metatarsal. All cadavers with gross pathology or radiographic fifth metatarsal pathology were excluded from the study. All procedures were performed by a fellowship trained orthopaedic foot and ankle surgeon. Results: All eleven cadavers met the inclusion criteria for this study. The average age of the patients was 66.6 +/- 20.1 years. There were five female feet and six male feet. There were seven right feet and four left feet. Distance from the percutaneous access site was measured to structures at potential risk. The closest structure at risk was the lateral dorsal cutaneous nerve (LDCN) (1.64 mm), which was contacted 2/11 times and transected both times. The extensor digitorum longus (EDL) and abductor digiti minimi (ADM) had no instances of contact during the procedure. Dissection allowed for the identification of structures at risk and the assessment of osteotomy. All procedures resulted in a complete osteotomy. Conclusion: Overall, distal percutaneous bunionette osteotomy is largely safe. Structures pertinent to the surgery were identified with ease and were intact after osteotomy with a Shannon burr. Anatomic variations of LDCN can present challenges to the procedure. Meticulous dissection and judicious use of fluoroscopy can help prevent further damage. Surgeons should be aware of anatomic variations in order to proceed safely.